Triticale improvement and production (Food and Agirculture Organization of the United Nations, 2004)
Triticale, the first successful human-made cereal grain, was deliberately produced in 1875 by crossing wheat with rye. Since then, the evolution of this crop has been the topic of keen interest for many plant scientists. This book presents updated information on various aspects of triticale production, improvement, uses and marketing strategies in the world. It also includes 13 country reports about triticale production and research status. In spite of the recent origin of this new crop and the limited research dedicated to its development, triticale inspires special attraction because of its good performance in stress environments and its diversified uses.